Structural and electronic features enabling delocalized charge-carriers in CuSbSe 2 - Yuchen Fu; Hugh Lohan; Marcello Righetto; Yi-Teng Huang; Seán R. Kavanagh; Chang-Woo Cho; Szymon J. Zelewski; Young Won Woo; Harry Demetriou; Martyn A. McLachlan; Sandrine Heutz; Benjamin A. Piot; et al. (Nature Communications)
Abstract Inorganic semiconductors based on heavy pnictogen cations (Sb3+ and Bi3+) have gained significant attention as potential nontoxic and stable alternatives to lead-halide perovskites for solar cell applications. A limitation of these novel materials, which is being increasingly commonly found, is carrier localization, which substantially reduces mobilities and diffusion lengths. Herein, CuSbSe2 is investigated and discovered to have delocalized free carriers, as shown through optical pump terahertz probe spectroscopy and temperature-dependent mobility measurements. Using a combination of theory and experiment, the critical enabling factors are found to be: 1) having a layered structure, which allows distortions to the unit cell during the propagation of an acoustic wave to be relaxed in the interlayer gaps, with minimal changes in bond length, thus limiting deformation potentials; 2) favourable quasi-bonding interactions across the interlayer gap giving rise to higher electronic dimensionality; 3) Born effective charges not being anomalously high, which, combined with the small bandgap ( $$\le$$ ≤ 1.2 eV), result in a low ionic contribution to the dielectric constant compared to the electronic contribution, thus reducing the strength of Fröhlich coupling. These insights can drive forward the rational discovery of perovskite-inspired materials that can avoid carrier localization.